Comparison of black-scholes models using historical volatility and garch volatility in collar strategy as hedging efforts for towr and tbig stocks - Brady Rikumahu; Mu’arif Fandhi Akhmad (Goodwood Publishing, 2023)
Purpose: This study aims to examine the implementation of option contracts using the Black-Scholes model with Historical Volatility and GARCH Volatility through a collar strategy, as a means of protecting stock value in the telecommunications sector. The research focuses on managing risk in stock investments, particularly for TOWR and TBIG stocks, in both crisis and non-crisis conditions. Research methodology: The study applies the Black-Scholes model using two types of volatility—Historical and GARCH—within a collar strategy framework to evaluate its effectiveness in mitigating risks associated with TOWR and TBIG stocks under varying market conditions. Results: For TOWR stocks, GARCH performs better in non-crisis conditions with three-month maturity, while Historical Volatility is superior in some shorter-maturity scenarios under both market conditions. For TBIG stocks, GARCH outperforms in all crisis scenarios with three-month maturity, whereas Historical Volatility leads in certain stable, short-term conditions. Conclusion: The effectiveness of volatility methods in the Black-Scholes model depends on stock type, market conditions, and maturity, with GARCH better for high volatility and longer terms, while Historical suits stable, short-term scenarios. Limitation: The study is limited to two telecommunications stocks and does not include empirical testing using live trading data, which could provide deeper validation of the proposed strategies. Contribution: This research contributes to the understanding of how investment strategies like collar options can be optimized using appropriate volatility models. Investment involves the allocation of money or capital with the aim of gaining profit.